2016
DOI: 10.1186/s12882-016-0338-z
|View full text |Cite
|
Sign up to set email alerts
|

The association of urinary sodium excretion and the need for renal replacement therapy in advanced chronic kidney disease: a cohort study

Abstract: BackgroundRestriction of dietary sodium is routinely recommended for patients with chronic kidney disease (CKD). Whether or not sodium intake is associated with the progression of CKD and mortality remains controversial. We evaluated the association of urinary sodium excretion (as a surrogate for sodium intake) on the need for renal replacement therapy and mortality in patients with advanced CKD.MethodsWe conducted a retrospective study of patients followed at a CKD clinic of a tertiary care hospital from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The outcomes examined were diverse: Six studies assessed mortality outcomes, four studies assessed morbidity outcomes, three studies assessed outcomes related to symptoms/quality of life/functional status, studies assessed BP outcomes; eight studies assessed other clinically relevant surrogate outcomes; and nine studies assessed physiologic outcomes (Table ) . A range of outcomes were captured by the studies considered lower quality, including all‐cause mortality, gastric cancer, end‐stage renal disease requiring dialysis or transplant, cardiovascular events, hypertension prevalence, headaches/migraines, quality of life, multiple sclerosis, BP, cognitive function, osteoporosis risk and prevalence, nonalcoholic fatty liver disease, type 2 diabetes, carotid atherosclerosis, bone mineral density, changes in left ventricular mass, inflammatory markers, albuminuria, and other urinary markers . Most of these studies (n = 40) found adverse effects of dietary salt on health outcomes and benefits of a sodium‐restricted diet on health, except for 7 that were neutral and one reported worsening symptoms with a sodium‐restricted diet in the elderly …”
Section: Resultsmentioning
confidence: 99%
“…The outcomes examined were diverse: Six studies assessed mortality outcomes, four studies assessed morbidity outcomes, three studies assessed outcomes related to symptoms/quality of life/functional status, studies assessed BP outcomes; eight studies assessed other clinically relevant surrogate outcomes; and nine studies assessed physiologic outcomes (Table ) . A range of outcomes were captured by the studies considered lower quality, including all‐cause mortality, gastric cancer, end‐stage renal disease requiring dialysis or transplant, cardiovascular events, hypertension prevalence, headaches/migraines, quality of life, multiple sclerosis, BP, cognitive function, osteoporosis risk and prevalence, nonalcoholic fatty liver disease, type 2 diabetes, carotid atherosclerosis, bone mineral density, changes in left ventricular mass, inflammatory markers, albuminuria, and other urinary markers . Most of these studies (n = 40) found adverse effects of dietary salt on health outcomes and benefits of a sodium‐restricted diet on health, except for 7 that were neutral and one reported worsening symptoms with a sodium‐restricted diet in the elderly …”
Section: Resultsmentioning
confidence: 99%
“…19-21 However, its association with renal function is less well investigated and confounding.Although several studies have shown that high dietary sodium intake increases the risk of CKD development or progression, 13,22-25 some results failed to find significant connections to renal outcome. 22,[26][27][28][29][30] In addition, although the adverse effects of increased dietary sodium on cardiovascular outcomes are more prominent in subjects with hypertension than in those without, 4,8,9 influence of hypertension on the relationship between sodium intake and CKD development is not known.…”
mentioning
confidence: 99%
“…Although several studies have shown that high dietary sodium intake increases the risk of CKD development or progression, 13,[22][23][24][25] some results failed to find significant connections to renal outcome. 22,[26][27][28][29][30] In addition, although the adverse effects of increased dietary sodium on cardiovascular outcomes are more prominent in subjects with hypertension than in those without, 4,8,9 influence of hypertension on the relationship between sodium intake and CKD development is not known. Therefore, in order to investigate whether dietary sodium intake affects CKD development, this study assessed a prospective community-based cohort of subjects with normal renal function with and without hypertension.…”
mentioning
confidence: 99%
“…Other reports have not indicated a significant association between urinary sodium and CKD progression or prognosis [18,19]. In addition, excessive salt restriction to less than 3 g per day increased the composite outcome of death and major cardiovascular events [20].…”
Section: Discussionmentioning
confidence: 96%